2016
DOI: 10.1107/s1600576716010347
|View full text |Cite
|
Sign up to set email alerts
|

Lattice strain and tilt mapping in stressed Ge microstructures using X-ray Laue micro-diffraction and rainbow filtering

Abstract: Micro-Laue diffraction and simultaneous rainbow-filtered micro-diffraction were used to measure accurately the full strain tensor and the lattice orientation distribution at the sub-micron scale in highly strained, suspended Ge micro-devices. A numerical approach to obtain the full strain tensor from the deviatoric strain measurement alone is also demonstrated and used for faster full strain mapping. We performed the measurements in a series of micro-devices under either uniaxial or biaxial stress and found an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
(69 reference statements)
1
14
0
1
Order By: Relevance
“…A robust, although time-consuming, technique for the local measurement of intra-granular strains in the bulk at micrometre spatial and 10 −4 strain accuracy is Differential Aperture X-ray Microscopy (DAXM) (Larson et al, 2002;Levine et al, 2006;Robach et al, 2013;Tardif et al, 2016) [32,33,34,35], a variant of polychromatic X-ray Laue micro-diffraction. More recently, using monochromatic micro-beam scanning, a far-field detector and an established 3DXRD indexing procedure (ImageD11) (Wright, 2017) [36], Hektor et al has shown local sensitivity of the method to hydrostatic strain (Hektor et al, 2019) [37], and Hayashi et al has demonstrated mapping the full strain tensor over a region containing 37 3 voxels at 1.2 µm spacing deep inside a steel specimen (Hayashi et al, 2019) [38].…”
Section: Intragranular Strain (Type III Stresses)mentioning
confidence: 99%
“…A robust, although time-consuming, technique for the local measurement of intra-granular strains in the bulk at micrometre spatial and 10 −4 strain accuracy is Differential Aperture X-ray Microscopy (DAXM) (Larson et al, 2002;Levine et al, 2006;Robach et al, 2013;Tardif et al, 2016) [32,33,34,35], a variant of polychromatic X-ray Laue micro-diffraction. More recently, using monochromatic micro-beam scanning, a far-field detector and an established 3DXRD indexing procedure (ImageD11) (Wright, 2017) [36], Hektor et al has shown local sensitivity of the method to hydrostatic strain (Hektor et al, 2019) [37], and Hayashi et al has demonstrated mapping the full strain tensor over a region containing 37 3 voxels at 1.2 µm spacing deep inside a steel specimen (Hayashi et al, 2019) [38].…”
Section: Intragranular Strain (Type III Stresses)mentioning
confidence: 99%
“…10 The bridge geometry was chosen so as to obtain an homogeneous, pure tetragonal strain in the central region. 41 The process used brought the whole released structure into contact with the silicon substrate, allowing further lithographic steps on the sample (figure 1.c).…”
Section: Strained Micro-bridges Fabricationmentioning
confidence: 99%
“…With the tunable-energy mode, the focusing of the beam on the sample surface may change during the measurements. Accuracies close to 10 À4 were obtained on Áa=a in Ge single-and UO 2 polycrystals (Robach et al, 2013) and a full strain analysis was performed in stressed Ge microstructures (Tardif et al, 2016). Measurements with a two-dimensional energy dispersive X-ray CCD detector in a strained copper single crystal have demonstrated the advantages of single-shot acquisitions for determining the components of the full strain tensor (Abboud et al, 2017).…”
Section: Introductionmentioning
confidence: 87%